The effect of extraction temperature and the type of solvent on the phenolic content, anti -oxidant capacity and flow indicators for the mucilage extracted from the root of the Althaea SP (Latakia University Journal -Biological Sciences Series, 2023)
This study was carried out   in Scientific Agricultural Research Center in Lattakia- Tishreen University in the period between 2021-2022, The study aimed to show the effect of the incubation temperature and the type of solvent used to extract the mucilage powder of the marshmallow root, on its content of phenols, its antioxidant capacity and flow indicators, by applying six treatments in the extraction, at a rate of three replicates, which are (Water at room temperature + isopropanol A, water at 40 °C ˚ + isopropanol B, water at 60 °C + isopropanol C, room temperature water + ethanol D, water at 40 °C ˚ + ethanol E, water at 60 °C ˚ + ethanol FThe results of the study and the statistical analysis at a significant level of 1% showed that increasing the incubation temperature positively affected both the phenolic content and the antioxidant capacity of the produced powder when using both solvents in the extraction, as well as the values ​​in the treatments resulting from the use of isopropanol were higher than those resulting from the use of ethanol . Treatment C (60°C and isopropanol) had the highest value for both phenolic content and antioxidant capacity, and they were 60 mg/100 g and 55.66%, respectively. Concerning the flow indicators of the studied powder, the incubation temperature did not affect the flow indicators values, while the type of solvent affected them. The values ​​of Hausner's index and compressibility index were good, with the highest value reaching 1.17 and 17.64%, respectively. The previous results indicate that Althaea root colloidal powder(mucilage) can be considered as a functional antioxidant and food additive that can be used in products that require nutrient flow due to its good flow indicators.